TINJAUAN HUKUM BISNIS TERHADAP PERLINDUNGAN DESAIN INDUSTRI DALAM UNSUR KEBARUAN YANG TELAH TERDAFTAR - Fitriyani Pakpahan, Elvira; O.K. Isnainul; Kesuma Wijaya, Emil (Penerbit Lafadz Jaya, 2025)
Industrial Design is a form of legal protection for the external appearance or visual form of a new product, which can be in the form of lines, patterns, colors, or a combination of these elements that give an aesthetic and functional impression to the product. This research discusses the limitations of the element of novelty in canceling registered industrial design rights. Law Number 31 of 2000 concerning Industrial Designs only states that an industrial design is considered new if at the date of application the design is not the same as a previously registered industrial design. The phrase